Pipeline End Manifold (PLEM) Structural Response Analysis due to the Settlement Process - Darobi, Ichwandanny Faturahman; Murdjito, Murdjito; Ikhwani, Hasan (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
Pipeline End Manifold (PLEM) is an offshore structure that consists of a simple subsea manifold that combines two or more pipelines into one pipeline. Like other offshore structures, the risk of seabed settlement may occur, and settlement is predicted can increase the stress of pipe and frame members. Stress that exceeds the allowable stress of codes may be a danger. So, stress analysis of the UC ratio of pipe and frame PLEM due to the settlement must be done. Stress analysis is performed using the numerical method with the model in FEM software. UC ratio refers to AMSE B31.8 2010 for pipe and API RP 2A (WSD) 22ed 2014 for the structural frame. From this analysis, the allowable settlement of pipe codes is at a depth below 450.42 mm. The deeper the settlement, the more stress the member frame increases. At a depth of 600 mm settlement, the greatest stress, 133.125 N/mm^2, UC 0.375, is found on member E04(L). According to the pipe codes, the maximum slope is 2.27˚ on the southward slope. The biggest effect of tilt settlement on the member frame is found in the west direction at member E04(U) with a value of 244.6 N/mm^2, UC 0.689, tilt settlement 3˚.